Agricultural income and prices. The interdependence of selected phenomena in Poland compared to EU-15 member states - Andrzej Czyżewski; Łukasz Kryszak (Managerial Economics)
The aim of this paper was to analyze the changes in various agricultural income measures in Poland since 2004 as compared to the situation of the EU-15 member states. Another objectivewas to examine the mentioned changes against prices. The main source of income data was the FADN database. Incomes of agricultural holdings in Poland are significantly lower than of those in most of the analyzed member states; however, this is the result of their smaller average area – their efficiency per hectare is relatively high. Polish agricultural holdings are also characterized by their comparatively small dependence on payments (although this is growing). Agricultural incomes are highly unstable, which refers to changes in price relations. This instability is particularly evident in countries with smaller farms and, thus, lower income per farm.